A novel surgical management for pediatric patients with irreducible atlantoaxial dislocation: Transoral intraarticular cage distraction and fusion with C-JAWS staple fixation - Zou, Xiaobao; Yang, Haozhi; Fu, Suochao; Deng, Chenfu; Chen, Junlin; Ma, Rencai; Ma, Xiangyang; Xia, Hong (Frontiers in Surgery, 2023)
Background: Currently, irreducible atlantoaxial dislocation (IAAD) can be treated by a single transoral approach in one stage to reduce surgical injuries to patients. However, the widely used fixation devices are not suitable for pediatric patients because of larger profile of devices. Objective: The purpose of this study is to report the preliminary clinical outcomes of a novel surgical technique by transoral intraarticular cage distraction and fusion with C-JAWS staple fixation for pediatric patients with IAAD. Methods: From June 2011 to June 2014, eight pediatric patients with IAAD were enrolled and treated by this technique in our department. Patients’ clinical data were retrospectively analyzed, including neurological status, clinical symptoms, reduction, bone fusion, and complications. Results: The surgeries were successfully performed in all patients without injuries to spinal cord, nerve and blood vessel. Clinical symptomatic relief was presented on all 8 patients (100%). Satisfactory reduction was indicated by significant decrease of atlanto-dental interval postoperatively (P < 0.05). The remarkable improvement of postoperative neurological function has been proved by significant increase of Japanese Orthopaedic Association score (P < 0.05). The average follow-up duration was 19.4±5.8 months (range 12–30 months). Bone fusion was achieved in all 8 cases. No complications were documented after operation and during follow-up. Conclusions: Transoral intraarticular cage distraction and fusion with C-JAWS staple fixation is an effective treatment for pediatric patients with IAAD, which can achieve satisfactory reduction, fixation and bone fusion.